The Theoretical Description for Sucralose and Alitam Food Sweeteners Electrochemical Determination by CoO(OH)/CoO2 Redox Pair - Tkach, V. V.; Storoshchuk, N. M.; de Oliveira, S. C.; Ivanushko, Ya. G.; Biryuk, I. G.; Sykyrytska, T. B.; Yagodynets, P. I.; da Silva, A. O.; Masna, Z. Z.; Shevchenko, I. M.; Gnitsevych, V. A.; Yudina, T. I.; et al. (My University, 2025)
Abstract: For the first time, the electrochemical determination of sucralose and alitam on the anode, modified by cobalt (III) oxyhydroxide, paired with tetravalent cobalt oxide, has been described theoretically. Sucralose electrooxidation by tetravalent cobalt derivative is caused by hydroxymethyl group oxidation, whereas alitam is oxidized by both primary amine and thioether sulfur. The correspondent mathematical model analysis has shown that the steady-state stability range is wider than in most systems of electrochemical determination due to the fragile ionization of both analytes in a neutral medium. For this reason, the CoO(OH)/CoO2 redox pair may be efficiently used for the electrochemical determination of both sucralose and alitam.
Keywords: sucralose; alitam; cobalt(III) oxyhydroxide; electrochemical sensors; stable steady-state